Gendered discourses - Sunderland, Jane (Palgrave Macmillan, 2004)
This advanced textbook critically reviews a range of theoretical and empirical work on gendered discourses and explores how gendered discourses can be identified, described and named. It also examines the actual workings of discourses in terms of construction and their potential to 'damage'.